A gender stratified controlled descriptive study to identify how specific food and drink consumption differentiate in MS - Delikanlı Akbay, Gülşen; Karakullukçu, Erdinç; Akyol Mutlu, Aslı (Progress in Nutrition, 2021)
Objective: There is an ongoing research on the idea that certain diets could make a difference in Multiple Sclerosis (MS) symptoms and progression. This study aimed to investigate the consumption rates of certain food and drinks in MS patients. The association between the presence of MS and the body mass index, sleeping duration, obesity status was also examined.Methods: The study was designed as a controlled descriptive study, consisting of 229 females (134 MS patients, 95 healthy volunteers) and 163 males (62 MS patients, 101 healthy volunteers). Blood samples were collected for biochemical evaluation of 25-hydroxyvitamin D (25(OH)D). Obesity status of the participants was determined. Average 24-hour retrospective food and drink consumption rates were collected. To identify factors associated with MS, multivariate logistic regression analyses were applied for both male and female data.Results: Increase in 25(OH)D level was associated with decrease in the odds of having MS. Women were more likely to experience MS if they preferred to wear head and body-covering clothes in their daily lives. For both male and females, increase in the individual consumption rate of herbal tea and coffee was associated with a reduction in the likelihood of having MS. Moreover, men who sleep half an hour more in a day were 16.5% less likely to have MS, adjusted for other factors considered in this study.Conclusion: Based on the findings of this study, nutrition contents of the food and drinks associated with MS can be detected, and dietary precautions might be taken.